Impact Of Social Media On Wellbeing Of Elderly Using Stressor-Strainoutcome Model - Shamugam, Lalitha (2024)
National statistics department, malaysia reported malaysia’s population aged 60 years and above are increasing over the years from 5.2% in 1970 to estimated 15 % in 2035. Due to this increase, the influence of social media usage like facebook or whatsapp towards the elderly is becoming more significant. From the literature, it clearly highlights the benefits gained from using internet, particularly social media, by elderly and how this positively impacting their subjective wellbeing (swb). However, there is limited literature with almost no data on what happen when elderly feel exhausted with social media usage and how it is negatively impacting their swb. Hence, this study addressed the gap in existing literature by examining the precursors of social media fatigue and its relationship with passive social media usage. To achieve these objectives, a conceptual model based on stressor-strain-outcome (sso) is developed to explain these relationships. The study further investigated the impact of sso on the swb of the elderly to understand whether social media usage increase or decrease their swb. Purposive sampling method was used in this study to randomly select elder adults aged 60 years and above with social media such as facebook or whatsapp. Self-administered questionnaires were used for gathering data from the respondents. Multiple methods of data collection were employed, whereby some questionnaires were mailed to the respondents, some were personally administered because the sample consist of elder adults. This study used the partial least squares (pls) and structural equation modelling (sem) tool to examine the identified constructs and their relationships between one another.